Perancangan Alat Ukur Kelembaban Tanah Media Tanaman Hias Menggunakan Sensor YL-69 Berbasis Arduino Uno - Andriansyah Murasyd; M. Rizky Azhari; Amar Abdullah; Sri Muryani (Universitas Bina Sarana Informatika, 2022)
Soil moisture is water that fills part or all of the soil pores above the water table. Another definition states that soil moisture states the amount of water stored between soil pores is very dynamic, this is caused by evaporation through the soil surface. Soil moisture is used for water resource management, early warning of drought and irrigation scheduling. Lack of water in soil moisture can cause wilting in plants and timely corrective action through watering/irrigation can save plants. Decorative plants are plants that are maintained because of the beauty of their flowers. Plants that have a beauty value in terms of shape, leaf color, crown and flowers, are often used to decorate the yard and so on. Reporting from Republika.co.id, during the Covid-19 pandemic, buyers, namely plant lovers, came to buy various decorative plants, the sales turnover increased sharply, reaching an average of 300 percent from usual. Examples of decorative plants that are suitable for planting in dry soil are cacti, moist soil is suplir plants, while wet soil is ivory betel. If the soil temperature shows a temperature of 0° - 40°C then the value of dry soil moisture, a temperature of 40° - 70°C indicates the value of moist soil moisture, and a temperature of 70° - 100°C indicates the value of wet soil moisture. Based on this description, a research was made with the title design of soil moisture measuring instruments in plants using an arduino uno-based yl-69 sensor on decorative plant media. In this study, the main components used are Arduino Uno microcontroller, NodeMCU, LCD and YL-69 Soil Moisture Sensor. This tool will also be connected to a Smartphone via wi-fi using the Blynk application which will display information about the measured soil moisture temperature. The purpose of making this tool is to make it easier to monitor and control the temperature of soil moisture and distinguish between dry and wet soil temperature levels.